Association between periodontal disease and schizophrenia: a bidirectional two-sample Mendelian randomization study - Cao, Hongliang; Wu, Hao; Wang, Pengyu; Zhang, Haiyang; Wang, Song (Scientific reports, 2024)
The connection between periodontal disease (PD) and schizophrenia (SCZ) has been reported in observational studies, but it remains unclear. This research aims to examine the bidirectional causal impacts between PD and SCZ. The FinnGen consortium supplied summarized data on PD for 346,731 individuals (87,497 cases and 259,234 controls) of Finnish ancestry, and information on SCZ was acquired from the OpenGWAS repository, encompassing 127,906 individuals (52,017 cases and 75,889 controls) of European ancestry. Next, we conducted Mendelian randomization (MR) analysis to establish a causal inference relationship between PD and SCZ. The inverse variance weighted (IVW) method was utilized as the primary analysis. Additionally, some sensitivity analyses were utilized to verify the stability of the results. The analysis of IVW results indicated no impact of PD on SCZ (IVW OR = 1.10, 95% CI 0.97–1.24, P = 0.14). Nevertheless, the inverse relationship between PD and SCZ was identified through reverse MR analysis (IVW OR = 1.03, 95% CI 1.01–1.05, P = 0.002). The findings from MR-Egger, weighted median, simple mode, and weighted mode approaches aligned with the outcomes of the IVW method. Based on sensitivity analyses, horizontal pleiotropy is unlikely to distort causal estimates. This study presented the initial proof of a genetic causal relationship between SCZ and PD, albeit with a minimal impact. Further exploration is needed to gain a deeper understanding of this relationship. Furthermore, no genetic causal relationship between PD and SCZ was identified.